Clinical impact of prolonged diagnosis to treatment interval (DTI) among patients with oropharyngeal squamous cell carcinoma. (May 2016) - Sharma, Sonam; Bekelman, Justin; Lin, Alexander; Lukens, J. Nicholas; Roman, Benjamin R.; Mitra, Nandita; Swisher-McClure, Samuel
Highlights: We examined factors for treatment delays in oropharyngeal squamous cell carcinoma. We observed significantly worse overall survival with delays greater than 30 days. We found disparities in diagnosis to treatment interval by socioeconomic factors. Facility level factors (case volume and IMRT) also increased the risk of delay. These findings should be considered to develop more efficient care pathways. Summary: Purpose/objective(s): We examined practice patterns using the National Cancer Data Base (NCDB) to determine risk factors for prolonged diagnosis to treatment interval (DTI) and survival outcomes in patients receiving chemoradiation for oropharyngeal squamous cell carcinoma (OPSCC). Methods and materials: We identified 6606 NCDB patients with Stage III–IV OPSCC receiving chemoradiation from 2003 to 2006. We determined risk factors for prolonged DTI (>30 days) using univariate and multivariable logistic regression models. We examined overall survival (OS) using Kaplan Meier and multivariable Cox proportional hazards models. Results: 3586 (54.3%) patients had prolonged DTI. Race, IMRT, insurance status, and high volume facilities were significant risk factors for prolonged DTI. Patients with prolonged DTI had inferior OS compared to DTI ⩽ 30 days (Hazard Ratio (HR) = 1.12, 95% CI 1.04–1.20, p = 0.005). For every week increase in DTI there was a 2.2% (95% CI 1.1–3.3%, p < 0.001) increase in risk of death. Patients receiving IMRT, treatment at academic, or high-volume facilities were more likely to experience prolonged DTI (High vs. Low volume: 61.5% vs. 51.8%, adjusted OR 1.38, 95% CI 1.21–1.58; Academic vs. Community: 59.5% vs. 50.6%, adjusted OR 1.26, 95% CI 1.13–1.42; non-IMRT vs. IMRT: 53.4% vs. 56.5%; adjusted OR 1.17, 95% CI 1.04–1.31). Conclusions: Our results suggest that prolonged DTI has a significant impact on survival outcomes. We observed disparities in DTI by socioeconomic factors. However, facility level factors such as academic affiliation, high volume, and IMRT also increased risk of DTI. These findings should be considered in developing efficient pathways to mitigate adverse effects of prolonged DTI.